DEVELOPMENT OF FLIPPED CLASSROOM LEARNING INSTRUMENT AS INNOVATIVE LEARNING WHICH INTEGRATED TO YOUTUBE VIDEO TO IMPROVE STUDENT LEARNING ACHIEVEMENT - ZAHIDIN AINUR ROSYID, HANIF; , MADLAZIM (Inovasi Pendidikan Fisika, 2019)
This research departs from physics lessons problem which is considered as difficult by most of Indonesian students. So students are rarely interested in studying physics at home or even to paying attention to in class physics lessons. Using YouTube technology that begins to enter in educational sector, the teacher could use this opportunity to increase the student interest of learning physics using YouTube videos. Thus, teacher needs a learning instrument of certain model to make the media usage more practical and effective. Therefore, learning instruments is developed through ASSURE method. The result of this development has been confirmed to be valid by two expert validators, then the instruments tested on Senior High School of Darul Ulum Medali Sugio?s third grade student, resulting a good result proofing the good practicability of the instrument. The effectiveness of these instruments also proven to significantly improve student learning achievement. After the limited test, researchers get a positive response from students to be able to continue learning by using the same model and instruments that has been developed. Keywords : Flipped classroom learning models, YouTube videos, improve learning Achievement